Management of Staphylococcus aureus Bloodstream Infections - Kimmig, Aurelia; Hagel, Stefan; Weis, Sebastian; Bahrs, Christina; Löffler, Bettina; Pletz, Mathias W. (Frontiers in Medicine, 2021)
Staphylococcus aureus bloodstream infections are associated with a high morbidity and mortality. Nevertheless, significance of a positive blood culture with this pathogen is often underestimated or findings are misinterpreted as contamination, which can result in inadequate diagnostic and therapeutic consequences. We here review and discuss current diagnostic and therapeutic key elements and open questions for the management of Staphylococcus aureus bloodstream infections.